Conservation laws for a modified lubrication equation. (December 2015) - Wei, Long
Abstract: In this work we study the conservation laws of a modified lubrication equation, which describes the dynamics of the interfacial motion in phase transition. We show that the equation is nonlinear self-adjoint and has an exact Lagrangian with an auxiliary function. As a result, by a general theorem on conservation laws proved by Nail Ibragimov recently and Noether's theorem, some new conservation laws for the equation are obtained. Our results show that the non-locally defined conservation laws generated by Noether's theorem are equivalent to the local ones given by Ibragimov's theorem.